Liberty - Larson, Kirby (New York : Scholastic Press, 2016)
In 1940s New Orleans, Fish Elliot is a polio-survivor with a knack for inventing and building things, and his African American neighbor Olympia is a girl with a talent for messing things up, but they are united in an effort to save a starving stray dog they call Liberty--and when Liberty is caged by a nasty farmer, they find an unlikely ally in a German prisoner of war, Erich, who is not much older than the two children.
School Library Journal, August 2016
Kirkus Starred, August 2016
4.9
3-6
640L
Keywords: Dogs -- Fiction; People with disabilities -- Fiction; Family life -- Louisiana -- Fiction; African Americans -- Fiction; Prisoners of war -- Fiction; Race relations -- Fiction; Friendship -- Fiction; World War, 1939-1945 -- Fiction; New Orleans (La.) -- History -- 20th century -- Fiction; Dogs -- Fiction; People with disabilities -- Fiction; Family life -- Fiction; African Americans -- Fiction; Prisoners of war -- Fiction; Race relations -- Fiction; Friendship -- Fiction; World War, 1939-1945 -- Fiction; New Orleans (La.) -- History -- 20th century -- Fiction